Prophylactic Antibiotic Pattern in Open Reduction Internal Fixation for Closed Fractures at Dr. Hasan Sadikin General Hospital Bandung in 2013 - Edwiza, Deviana Suciani; Husen, Ike Rostikawati; Arsa, Widya (Althea Medical Journal, 2017)
Background: Surgical site infection remains a serious complication of a surgery. Prophylactic antibiotics should be used in open reduction and internal fixation to prevent surgical site infection. This study aimed to study the pattern of prophylaxis used in internal fixation of closed fractures as this surgery is considered as a high-risk orthopedic procedures.Methods: This retrospective-descriptive study was performed from August to October 2014. Subject was closed fracture patient who underwent open reduction and internal fixation at Dr. Hasan Sadikin General Hospital Bandung in 2013. Data about characteristics of patients and pattern of the use of prophylactic antibiotics were obtained from patientsâ medical record.Results: Medical records from 76 patients who underwent ORIF were analyzed.Â  Sixty eight patients (68.4%) were given 1 gram cefazolin intravenously as preoperative antibiotic prophylaxis. Timing for administration of antibiotics was 30â60 minute preoperatively in 34 (44.2%) patients. All Patients were given postoperative prophylaxis for 4.09 Â± 1.36 days in average. The antibiotic most commonly used was cefazolin in 51 (63%) patients. All patients were prescribed an oral antibiotic at discharge. Cefadroxil was the most common antibiotic prescribed for patients at discharge. Conclusions: Cefazolin is the most common preoperative prophylactic antibiotic given to patients. All Patients are given postoperative prophylaxis and prescribed an antibiotic at discharge.Â